Mikro nepravilnosti kovinskih površin - Miko, Edward (Strojniški vestnik, 2005)
It has been established that machining parameters such as feed per tooth, rotational speed, tool path interval and cutter setting angle can influence the surface roughness during ball-end milling. A scanning electron microscope (SEM) was used to register and analyze the morphology of milled surfaces. SEM photographs of the surfaces with longitudinal and lateral profiles are included and discussed. The influence of the machining factors on the geometrical microstructure of the surface is also evaluated. A frequency analysis of the profiles of surfaces milled with a ball-end cutter is presented. The investigations show that the tool path interval has a considerable effect on the roughness of the milled surfaces.
Keywords: frezanje oblikovno; obdelave površin; nastavljanje frezal; morfologija površin; frezanje; površine; napake; morfologija; lastnosti